Evaluasi Perwali Surabaya No.81 Tahun 2021 Tentang Bidang Angkutan (Suroboyo Bus) dalam Mengurangi Kemacetan di Kota Surabaya - Ian Daksana, Kumara Adyatma; Murti, Indah; Hariyoko, Yusuf (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
Congestion is a phenomenon where traffic is blocked due to a dense volume of vehicles. This means that congestion is an inadequate condition of a road section compared to the volume of existing vehicles. This is what is driving the Surabaya City Government to prepare public transportation services that operate as public transportation with integrated routes in a number of areas of the City of Surabaya. However, the research results show that the Suroboyo Bus is still not optimal in meeting people's daily mobility needs. And there are also several problems that need to be fixed, especially regarding bus waiting times. This study concludes that the development and improvement of Suroboyo Bus services needs to continue to be carried out to achieve the goal of reducing congestion and improving the quality of public transportation in Surabaya.